Stressful situations at police work - Valickas, Gintautas; Vabolytė, Kristina (Psichologija, 2002)
The article examined the most stressful situations in police force. Subjects included 347 police officers from various Lithuanian cities. The special questionnaire was developed to asess the stressful situations at police work. Results show that police officers experience internal (general and specific) as well as external sources of stressors. Both specific for police work and common stressful situations could cause the most level of tension. Police officers’ sex, rank, particular police department and length of service are the factors which influence set of the most stressful situations for particular policeman.